Kung fu hustle [videorecording (DVD)] = [Gong fu] - Zhou, Xingchi, 1962-; Yuan, Hua, 1950-; Yuan, Qiu (Sony Pictures Home Entertainment, 2007)
Sing is a hapless, small-time gangster who is desperate to join the evil Axe Gang. When he stumbles into a local slum, his cocky behavior sparks an epic Kung Fu showdown between the town's landlords and the all-powerful Ax Gang. As the battle erupts, an unlikely hero transforms into the greatest Kung Fu master of all.